Horseshoe kidney – a case report - Rao, Ephraim Vikram; Battula, Sadanand (International Journal of Research in Medical Sciences, 2017)
Horseshoe kidney is a rare non-fatal congenital malformation of renal development. It usually remains asymptomatic and in many cases it is discovered incidentally. This anomaly is found twice as often in men than in women. The present report, horseshoe kidney was discovered in 62-year-old male cadaver during routine dissection. The inferior poles of the kidneys were fused to form a parenchymatous isthmus, resulting in a horseshoe kidney. The horseshoe kidney was located anterior to the abdominal aorta and the inferior vena cava at a level lower than the normal kidney. Both renal hila were directed anteriorly and the ureters which drained from each renal pelvis descended anterior to the isthmus to enter the urinary bladder normally. There were 3 renal arteries, 1 on the right and 2 on the left. The inferior vena cava was behind the isthmus and the lower pole of the right kidney. Two renal veins opened independently into the inferior vena cava. It is important to be aware of this renal anomaly in clinical practice, especially during renal surgeries, renal transplants, or surgical and endovascular procedures on the aorta.